Myocardial deformation assessed among heart failure entities by cardiovascular magnetic resonance imaging. (4th February 2021) - Hashemi, Djawid; Motzkus, Laura; Blum, Moritz; Kraft, Robin; Tanacli, Radu; Tahirovic, Elvis; Doeblin, Patrick; Zieschang, Victoria; Zamani, S. Mahsa; Kelm, Marcus; Kuehne, Titus; Pieske, Burkert; et al.
Abstract: Aims: Although heart failure (HF) is a leading cause for hospitalization and mortality, normalized and comparable non‐invasive assessment of haemodynamics and myocardial action remains limited. Moreover, myocardial deformation has not been compared between the guideline‐defined HF entities. The distribution of affected and impaired segments within the contracting left ventricular (LV) myocardium have also not been compared. Therefore, we assessed myocardial function impairment by strain in patients with HF and control subjects by magnetic resonance imaging after clinically phenotyping these patients. Methods and results: This prospective study conducted at two centres in Germany between 2017 and 2018 enrolled stable outpatient subjects with HF [ n = 56, including HF with reduced ejection fraction (HFrEF), HF with mid‐range ejection fraction (HFmrEF), and HF with preserved ejection fraction (HFpEF)] and a control cohort ( n = 12). Parameters assessed included measures for external myocardial function, for example, cardiac index and myocardial deformation measurements by cardiovascular magnetic resonance imaging, left ventricular global longitudinal strain (GLS), the global circumferential strain (GCS) and the regional distribution of segment deformation within the LV myocardium, as well as basic phenotypical characteristics. Comparison of the cardiac indices at rest showed no differences neither between the HF groups nor between the control group and HF patients (one‐way ANOVA P = 0.70). The analysis of the strain data revealed differences between all groups in both LV GLS (One‐way ANOVA: P < 0.01. Controls vs. HFpEF: −20.48 ± 1.62 vs. −19.27 ± 1.25. HFpEF vs. HFmrEF: −19.27 ± 1.25 vs. −15.72 ± 2.76. HFmrEF vs. HFrEF: −15.72 ± 2.76 vs. −11.51 ± 3.97.) and LV GCS (One‐way ANOVA: P < 0.01. Controls vs. HFpEF: −19.74 ± 2.18 vs. −17.47 ± 2.10. HFpEF vs. HFmrEF: −17.47 ± 2.10 vs. −12.78 ± 3.47. HFrEF: −11.41 ± 3.27). Comparing the segment deformation distribution patterns highlighted the discriminating effect between the groups was much more prominent between the groups (one‐way ANOVA P < 0.01) when compared by a score combining regional effects and a global view on the LV. Further analyses of the patterns among the segments affected showed that while the LVEF is preserved in HFpEF, the segments impaired in their contractility are located in the ventricular septum. The worse the LVEF is, the more segments are affected, but the septum remains an outstanding location with the most severe contractility impairment throughout the HF entities. Conclusions: While cardiac index at rest did not differ significantly between controls and stable HF patients suffering from HFrEF, HFmrEF, or HFpEF, the groups did differ significantly in LV GLS and LV GCS values. Regional strain analysis revealed that the LV septum is the location affected most, with reduced values already visible in HFpEF and further reductions in HFmrEF and HFrEF.